1977
DOI: 10.1063/1.434450
|View full text |Cite
|
Sign up to set email alerts
|

The binding energy between NO and NO+

Abstract: The photoionization efficiency curve of the nitric oxide dimer (N0) 2 was obtained in the wavelength range from 1420$. to 1230~ (8.731 eV-10.080 eV). The ionization potential of (N0) 2 was found to be 8.752 eV ± 0.008 eV. From the structure of the photoion yield 2 + 1 +. curve of (N0) 2 , NO(II, V 11 =0)-NO (X E , v') 1s found to be bound when NO+(X 1 E+) is in the v'=O or 1 vibrational state. From this and the dissociation energy of (N0) 2 (0.069 eV ± 0~003 eV) obtained by• Billingsley and Callear, the dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 21 publications
1
36
1
Order By: Relevance
“…It suggests that the trans-(NO)2 dimer (Min4) is slightly more stable than the cis-(NO)2 dimer (Min8) in the presence of the Cu atom, whereas the cis-(NO)2 dimer is more stable than trans-(NO)2 in the gas phase. [30][31] However, according to the geometrical parameters shown in the Fig. 2, we can see that the N-O bond (1.351 Å) in the Min8 is one of the longest bonds in all of the minima structures, although the analogous N-O bond length (connected to the Cu atom) is 1.381 Å in the Min6.…”
Section: Resultsmentioning
confidence: 94%
“…It suggests that the trans-(NO)2 dimer (Min4) is slightly more stable than the cis-(NO)2 dimer (Min8) in the presence of the Cu atom, whereas the cis-(NO)2 dimer is more stable than trans-(NO)2 in the gas phase. [30][31] However, according to the geometrical parameters shown in the Fig. 2, we can see that the N-O bond (1.351 Å) in the Min8 is one of the longest bonds in all of the minima structures, although the analogous N-O bond length (connected to the Cu atom) is 1.381 Å in the Min6.…”
Section: Resultsmentioning
confidence: 94%
“…The 10% NO molecule seeded in He, with a backing pressure of 178 kPa, is introduced into the detecting chamber where the pressure becomes 22 µPa. Such expansion will generate the NO dimer whose concentration relative to monomer NO may be less than 1.2% obtained for pure NO molecules [8], and its dissociative photoionization (DPI) channel at 21.72 eV is unknown. Because of the small quantity of NO dimer in molecular beam, the N + dissociated from NO dimer ions are expected to contribute a little and almost all N + produced at this energy are processed as the production of the DPI of NO molecules.…”
Section: Methodsmentioning
confidence: 99%
“…The nitric oxide molecule is a common atmospheric species where both the neutral molecule and the cation have been implicated in such environmental problems as acid rain and ozone depletion. The cation, NO 1 , is present in the ionosphere and is thought to participate in the formation of proton hydrates as a consequence of sequential solvation by water molecules. In this context, there are interesting implications regarding the role of NO 1 X ions in the chemistry of the upper atmosphere, where X can be N 2 , CO 2 , or H 2 O, 7,17,[20][21][22] where several of these NO 1 X species are thought to act as precursors to the primary solvation step.…”
Section: Introductionmentioning
confidence: 99%
“…15 To complement the above experiments, it has recently been observed that (NO) n 1 cluster ions exhibit a very strong infrared transition within the wavelength range of a CO laser. 14,27 Smaller members of the pure (NO) n 1 series are quite strongly bound, 1,2,13 therefore their formation by electron impact from neutral clusters results in a significant degree of internal excitation (re 0 , the minimum binding energy). By the time ions reach the point of laser excitation, they are ca.…”
Section: Introductionmentioning
confidence: 99%